Optimalisasi pemanfaatan lahan kosong untuk meningkatkan ketahanan pangan santri di markaz penghafal Al-Quran Yayasan Layar Dakwah - Zurairah, Masdania; Refiza; Lubis, Muhammad Fiza; Rezeki, Rahmad; Saragih, Edy (Jurnal Derma Pengabdian Dosen Perguruan Tinggi (Jurnal DEPUTI), 2025)
Food security is a major challenge for Islamic boarding schools (pesantren) with limited resources and agricultural land. This study aims to optimize the use of vacant land to enhance food security at the Markaz Penghafal Al-Qur'an of Yayasan Layar Dakwah. The research methodology includes the application of agricultural techniques such as raised bed construction, selection of superior seeds, and efficient plant maintenance. The results show that utilizing vacant land with appropriate agricultural methods can increase food productivity and reduce dependence on external supplies. Tomato plants demonstrated the highest productivity at 2.25 kg/m², followed by red chili (1.75 kg/m²) and shallots (1.25 kg/m²). Additionally, the involvement of students in agricultural activities provided added benefits in terms of skill development and increased motivation. The novelty of this study lies in the integration of agricultural techniques with the pesantren education system, as well as the implementation of simple agricultural technologies that can be applied sustainably. Therefore, this research offers practical solutions to improve food security in pesantren and empower students in the field of agriculture.